2019
DOI: 10.1101/747840
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convergence of DNA methylation profiles in a novel environment in the reef coral Porites astreoides

Abstract: Phenotypic acclimatization is an organismal response to environmental change that may be rooted in epigenetic mechanisms. In reef building corals, organisms that are severely threatened by environmental change, some evidence suggests that DNA methylation is an environmentally responsive mediator of acclimatization. We investigated changes in DNA methylation of the reef coral Porites astreoides in response to simulated environmental change.Coral colonies were sampled from a variety of habitats on the Belize Bar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…cavernosa were methylated and primarily located in intergenic regions (>60% for all CpGs and methylated CpGs). This is comparable with the DNA methylation levels observed in other marine invertebrates (Gavery & Roberts, 2013; Strader et al, 2020; Venkataraman et al, 2020), including the relatively stress resistant corals Porites astreoides (Dimond & Roberts, 2020) and Montipora capitata (Trigg et al, 2021). Remarkably, methylation levels are significantly higher than those reported for the cnidarian model Aiptasia sp.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…cavernosa were methylated and primarily located in intergenic regions (>60% for all CpGs and methylated CpGs). This is comparable with the DNA methylation levels observed in other marine invertebrates (Gavery & Roberts, 2013; Strader et al, 2020; Venkataraman et al, 2020), including the relatively stress resistant corals Porites astreoides (Dimond & Roberts, 2020) and Montipora capitata (Trigg et al, 2021). Remarkably, methylation levels are significantly higher than those reported for the cnidarian model Aiptasia sp.…”
Section: Discussionsupporting
confidence: 78%
“…Epigenetic regulation is ubiquitous in all eukaryotes, based on the fundamental role that epigenetic mechanisms play in genome packing and functional organization within the cell nucleus. In corals, several studies have already reported evidence of epigenetic responses to different types of environmental stressors such as thermal stress, ocean acidification, and eutrophication, among others (Putnam et al, 2016; Liew et al, 2018; Dimond et al, 2017; Putnam et al, 2016; Liew et al, 2018; Rodriguez‐Casariego et al, 2018), as well as to broad environmental change (Rodríguez‐Casariego et al, 2020; Dimond & Roberts, 2020; Durante et al, 2019; Liew et al, 2020), with links to transcriptional plasticity (Dixon et al, 2018; Li et al, 2018). Since the symbiotic partners of corals also constitute part of (and therefore shape) their environment, the present work hypothesizes that transitions in these populations will require phenotypic acclimatory responses in the coral host, facilitated by epigenetic modifications.…”
Section: Introductionmentioning
confidence: 99%
“…However, by further comparing genome-wide summary statistics and PCAs at the individual level, we revealed the significant relationship between interindividual patterns in methylation and genetic variation, with 27% of variation in inter-individual methylation differences explained by genetic distance. Similar analyses have found significant correlations in reef-building coral (Dimond & Roberts 2020) and humans (Carja et al 2017). By only focusing on measures of population differentiation, previous marine invertebrate studies may have missed couplings between methylation and genetic patterns.…”
Section: Discussionsupporting
confidence: 69%
“…Whereas this does not necessarily indicate a bias in our methods, it highlights the need to account for the biological characteristics of a species when designing an experiment and evaluating results. Also when comparing across species, given genetic–epigenetic correlations, particularly in the case of DNA methylation and the requirement for a CpG sequence target site (Dimond & Roberts, 2020; Johnson et al, 2020), variation in genome architecture, gene number and content will impact the presence and use of DNA methylation as a mechanism of gene expression regulation.…”
Section: Discussionmentioning
confidence: 99%